The Effect of Buttock Therapy in Lowering the Level of Psychosomatic Symptoms and Improving Patient Attitude in Clients with Psychosomatic Symptoms - Nurjanah, Dian Siti; Rismanto, Firman (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
Psychosomatic is a psychological disorder that has an impact on physical disorders or vice versa that is often experienced by a person, but often the disorder is also ignored. Psychosomatics can be caused by various things, but in general it is caused by psychological stress that results in stress or anxiety. Psychosomatics can attack the weakest organs of the body when a person is facing psychological stress, the highest prevalence being hypertension and hypercholesterol. These conditions need to be addressed as early as possible. Therefore, the purpose of this study is to test the treatment of back acupuncture therapy in reducing the level of psychosomatic symptoms and improving patience in clients with psychosomatic symptoms. The research approach used is quantitative experiment with a pre-experiment design type. The pre-experiment design model used is one group pretest-posttest design. The research sample used was the entire client population with psychosomatic symptoms at the Totok Punggung Health Center, Jati Asih, Bekasi. The data collection techniques used were tests with pre-test and post-test instruments. The data analysis techniques used were descriptive analysis and hypothesis testing. Test the hypothesis using a paired sample t-test. The results of the descriptive analysis showed a decrease in psychosomatic symptoms pre-post back acupuncture therapy, namely pre-therapy which was in the low category by 32% and post-therapy by 72%. While patient attitudes also showed an improvement, pre-therapy which was in the high category by 57% and post-therapy by 62%. The results of the paired sample t-test showed a significance value of 0.000 < 0.05, therefore H0 was rejected and Ha was accepted. So it can be concluded that back acupuncture therapy has an effect in reducing the level of psychosomatic symptoms and increasing patience in clients with psychosomatic symptoms at Rumah Sehat, Jati Asih, Bekasi.